2018
DOI: 10.1177/0886260518760012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moral Disengagement on Bullying: Testing the Moderating Role of Personal and Social Factors

Abstract: Bullying is a subset of aggressive behavior that has severe consequences in children's psychosocial development. Bullying behaviors can be influenced by personal and social factors, such as gender, age, school type, and sport participation, as well as psychological constructs, such as moral disengagement. The present study was designed to investigate the effect of moral disengagement on bullying behaviors and the moderating role of personal and social factors. In this study, 2,252 students ( M = 13.57, SD = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
3
14
1
3
Order By: Relevance
“…Overall, the findings of the present study indicated that although moral disengagement is a strong predictor of willingness to cyberbully, its effect can be mediated by different constructs under different circumstances. Recently, Travlos et al (2018) demonstrated that different personal (i.e., gender and age) variables may influence the effect of moral disengagement on traditional bullying behavior. The present study including participants of different ethnic background, age and gender distribution, also suggested that such personal and cultural variables may be responsible for the differential processes found in predicting the decision to cyberbully.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the findings of the present study indicated that although moral disengagement is a strong predictor of willingness to cyberbully, its effect can be mediated by different constructs under different circumstances. Recently, Travlos et al (2018) demonstrated that different personal (i.e., gender and age) variables may influence the effect of moral disengagement on traditional bullying behavior. The present study including participants of different ethnic background, age and gender distribution, also suggested that such personal and cultural variables may be responsible for the differential processes found in predicting the decision to cyberbully.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism allows transgressing the code of ethics itself to perform behaviors, in principle unacceptable, in certain situations without feeling guilty. Thus, the positive relationship between moral disengagement and bullying perpetration are well documented (e.g., Bjärehed et al, 2020 ; Gini et al, 2020 ; Travlos et al, 2021 ), as indicated by recently developed meta-analyses (Gini et al, 2014 ; Killer et al, 2019 ). They show how bullying perpetrators trigger different mechanisms of moral disengagement to avoid feelings of guilt or shame.…”
Section: Introductionmentioning
confidence: 93%
“…The effect of moral disengagement on traditional bullying is clear ( Paciello et al, 2020 ; Romera et al, 2021a ; Travlos et al, 2021 ), while the relationship between moral disengagement and cyberbullying remains controversial ( Lo Cricchio et al, 2021 ). Firstly, the characteristics of offline and online moral disengagement and cyberbullying are different.…”
Section: Moral Disengagement and Cyberbullyingmentioning
confidence: 99%